Five-year molecular response and overall survival with first- and second-generation tyrosine kinase inhibitors in patients with chronic myeloid leukemia in the chronic phase: a prospective, observational study : SIMPLICITY - Mauro, Michael J.; Hehlmann, Rüdiger; Williams, Loretta A.; Goldberg, Stuart L.; Michallet, Mauricette; Gambacorti-Passerini, Carlo; Tang, Derek; DeGutis, Irene S.; McBride, Ali; Parsons, Lori; Montelongo, Monica; Cortes, Jorge E. (Leukemia and lymphoma, 2025)
SIMPLICITY (NCT01244750) was an observational study evaluating first-line (1 L) tyrosine kinase inhibitors (TKIs; dasatinib, nilotinib, imatinib) in patients with chronic myeloid leukemia in the chronic phase in routine clinical practice. At data cutoff (January 28, 2020), 810 prospective US patients were included/analyzed (dasatinib, 302; nilotinib, 264; imatinib, 244). Within 5 years, 95.4% of patients (dasatinib, 96.5%; nilotinib, 93.5%; imatinib, 95.9%) had major molecular response (BCR::ABL1 ≤ 0.1%), and 79.2% (dasatinib, 79.8%; nilotinib, 81.7%; imatinib, 75.9%) deep molecular response (MR4.5; BCR::ABL1 < 0.0032%) demonstrating major improvement during the study period. Of 734 patients followed for 5 years, 5-year overall survival rate was 89.8% (dasatinib, 92.9%; nilotinib, 88.6%; imatinib, 87.0%); similar to that in randomized studies. Patients who switched treatment had a poorer outcome regardless of TKI, indicating that non-kinase domain mutations may play a role. Despite missing data on outcomes in routine care, these results demonstrate excellent response and survival rates.
Gesehen am 02.10.2025